Modulation of the Gut Microbiota by Shen-Yan-Fang-Shuai Formula Improves Obesity Induced by High-Fat Diets - Wang, Zhen; Lu, Junfeng; Zhou, Jingwei; Sun, Weiwei; Qiu, Yang; Chen, Weihong; Gao, Yabin; Yang, Ruibing; Ai, Sinan; Liu, Zhongjie; Guo, Yingbo; Liu, Wei Jing; et al. (Frontiers in Microbiology, 2020)
Obesity and related metabolic disorders are associated with intestinal microbiota dysbiosis, disrupted intestinal barrier and chronic inflammation. Shen-Yan-Fang-Shuai formula (SYFSF) is a traditional Chinese herbal formula composed of Astragali Radix, Radix Angelicae Sinensis, Rheum Officinale Baill, and four other herbs. In this study, we identified that SYFSF treatment prevented weight gain, low-grade inflammation and insulin resistance in high-fat diet (HFD)-fed mice. SYFSF also substantially improved gut barrier function, reduced metabolic endotoxemia, as well as systemic inflammation. Sequencing of 16S rRNA genes obtained from fecal samples demonstrated that SYFSF attenuated HFD-induced gut dysbiosis, seen an decreased Firmicutes-to-Bacteroidetes ratios. Microbial richness and diversity were also higher in the SYFSF-treated HFD group. Furthermore, similar therapeutic effects and changes in gut microbiota profile caused by SYFSF could be replicated by fecal microbiota transfer (FMT). Taken together, our study highlights the efficacy of SYFSF in preventing obesity and related metabolic disorders. Its therapeutic effect is associated with the modulation of gut microbiota, as a prebiotic.